Community Resilience: Rumah Kaca dan Irigasi Tetes pada Pertanian Pekarangan Ibu Rumah Tangga dalam Ketahanan Pangan Perumahan - Lian Agustina Setiyaningsih; Ahmad Luthfi; Zaid Dzulkarnain Zubizaretta; Sufiyanto Sufiyanto; Priyo Dari Molyo (I-Com: Indonesian Community Journal, 2024)
This community service focuses on increasing community resilience through the introduction of greenhouse technology and drip irrigation systems for home garden farming among housewives in housing complexes. This initiative is to increase household food security, carried out in collaboration with the Sustainable Food Yard Group (P2L) of Greenliving Housing, Gadang Village, Malang City. The implementation methods include: identifying partner conditions, designing programs and technical implementation, implementation, and monitoring and evaluation. The application of these modern agricultural techniques not only reduces water use but also increases crop yields, contributing to the sustainability of the community as a whole. This program emphasizes the importance of environmental management, independence, and the role of women in fostering resilient communities that are able to face the challenges of food insecurity. The results show a significant positive impact on household food production, highlighting the potential for this practice to be adopted by the wider community.